Changes in cheek pressure following rapid maxillary expansion. - Halazonetis, D J; Katsavrias, E; Spyropoulos, M N (Eur J Orthod, 1994)
The purpose of the present investigation was to study the effects of rapid maxillary expansion on the pressures exerted by the cheeks on the maxillary arch. The sample consisted of 15 patients (five males, ten females) who received either a Hyrax or Haas type expansion appliance for treatment of a bilateral maxillary constriction of more than 5 mm. The median age of the sample was 12 years. Buccal pressures were measured at the upper first molar on the left and right side, before and after active expansion, and also after an average of 3-4 months of retention with the appliance in place. Buccal pressures on the maxillary first molar averaged approximately 3 g/cm2 before expansion and increased significantly to a value of approximately 9 g/cm2 after expansion. Pressure change was approximately 0.6 g/cm2 for each millimetre of expansion. During the 3-4-month period of stabilization of the appliance, the pressures remained at the post-expansion levels and no adaptation of the soft tissues was observed. These results lead to the conclusion that cheek pressures on the maxillary arch may be implicated in the relapse occurring after rapid expansion, even after the usual 3-month period of stabilization.
Keywords: Adaptation, Physiological; Adolescent; Analysis of Variance; Cheek; Child; Dental Arch; Dental Stress Analysis; Electromyography; Facial Muscles; Female; Humans; Male; Manometry; Maxilla; Molar; Orthodontic Appliances; Palatal Expansion Technique; pressure; Recurrence; Tongue; Transducers, Pressure